Bathymetry using Synthetic Aperture Radar (SAR) satellites - Wiehle, Stefan (2017)
Maritime SAR applications: Synthetic Aperture Radar (SAR) is an active remote sensing technology. Radar satellites emit and receive their own signals and, hence, do not need to rely on sunlight for their acquisitions. Another benefit compared to optical satellites is SARs ability to look through clouds, which means data acquisition is very reliable. Radar beams cannot penetrate water. However, the small ripple waves on the sea surface are enough to reflect the signals back to the satellite. In the maritime sector, SAR is currently being used for the detections of sea state, wind, oil spills, sea ice, icebergs and ships. These detection algorithms have been developed to run automatically in the receiving station to provide results in Near Real Time (NRT). Applications are the improvement of wave and wind models by providing data across large areas, the improvement of maritime domain awareness, and the support of vessels travelling through ice-infested waters. With the BASE-platform project, bathymetry is added to this list of maritime SAR applications.